A study on modelling cochlear duct mid-scalar length based on high-resolution computed tomography, and its effect on peri-modiolar and mid-scalar implant selection. Issue 9 (19th August 2019) - Pamuk, G; Pamuk, A E; Akgöz, A; Öztürk, E; Bajin, M D; Sennaroğlu, L
Abstract: Objective: To determine cochlear duct mid-scalar length in normal cochleae and its role in selecting the correct peri-modiolar and mid-scalar implant length. Methods: The study included 40 patients with chronic otitis media who underwent high-resolution computed tomography of the temporal bone. The length and height of the basal turn, mid-modiolar height of the cochlea, mid-scalar and lateral wall length of the cochlear duct, and the 'X' line (the largest distance from mid-point of the round window to the mid-scalar point of the cochlear canal) were measured. Results: Cochlear duct lateral wall length (28.88 mm) was higher than cochlear duct mid-scalar length (20.08 mm) ( p < 0.001). The simple linear regression equation for estimating complete cochlear duct length was: cochlear duct length = 0.2 + 2.85 × X line. Conclusion: Using the mid-scalar point as the reference point (rather than the lateral wall) for measuring cochlear duct mid-scalar length, when deciding on the length of mid-scalar or peri-modiolar electrode, increases measurement accuracy. Mean cochlear duct mid-scalar length was compatible with peri-modiolar and mid-scalar implant lengths. The measurement method described herein may be useful for pre-operative peri-modiolar or mid-scalar implant selection.